Effect of Using Zingiber officinale and Vitamin E on some Reproductive traits of Awassi Male Lamb: Mudhaffar N.R.Al-Saigh1 and Saad Th. J. Al-Rawi2 - Al-Saigh, Mudhaffar N.R. (The Iraqi Journal of Veterinary Medicine, 2012)
This study was aimed to find out the effect of Zingiber 2.5% and vit.E(administrated a dose of 400mg/head) on some reproductive traits of 18Awassi male lambs. Divided randomly into three groups equally. The resultshowed significant (P<0.05) increase in serum testosterone concentration andsemen traits in animals group one which received ginger and group two wherethe animals received vit E and ginger comparing to the control group , thatvit.E gave better results in these measurements in group two.